Problematik Disparitas Penjatuhan Pidana Penjara Subsidair Uang Pengganti dalam Tindak Pidana Korupsi (Solusi untuk Penyelesaian) - Imanuel Lawalata; Jessyca Haniel Picauly (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article analyzes the problems and challenges faced by corruptors sentenced to prison terms in lieu of compensation. Using an empirical legal approach based on literature studies and combined with interviews, the findings reveal that, in decisions 37/Pid.Sus-TPK/2025/PN Amb and decision number 18/Pid.SusTPK/2024/PTAmb. In both cases, the sentence is one year in prison in lieu of compensation, but the compensation in both cases has a different nominal value. Suggestions can be submitted to the Supreme Court to issue a Supreme Court Circular regarding prison terms in lieu of compensation to serve as a guideline for judges in corruption cases in handling these issues.